Syllabus Mining for Information Literacy Instruction: A Scoping Review - Butler, Kathleen; Calcagno, Theresa (Evidence Based Library and Information Practice, 2020)
Background - The course syllabus is a roadmap to curriculum development and student learning objectives providing valuable information to assist library instruction. This scoping review examines research that uses syllabus mining to track Information Literacy concepts and skills in academic settings.Objectives - The present study uses a scoping methodology to examine syllabus mining of Information Literacy with the focus of analysis on the methodologies employed in syllabus review and the recommendations from the studies.Design - Searches of databases of literature from librarianship and education, as well as a multidisciplinary database, yielded 325 journal articles. Inclusion criteria specified peer-reviewed articles from any year, and excluded grey literature. After removing duplicates, 2 reviewers screened titles and abstracts and reviewed full text, yielding 17 studies to analyze.Results - Characteristics of the included studies, methodology, and recommendations were charted by two reviewers. All studies reported retrieving information that increased opportunities for collaboration with instructors and targeted engagement with students, and seven themes were identified.Conclusions - Instructional librarians should be encouraged to conduct syllabus studies to increase collaboration with faculty to develop coursework, to meet student information needs in a strategic manner, and to identify discipline-specific Information Literacy concepts.